PENGARUH SISTEM PENGGAJIAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN - Permana, Dwi Panji; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the payroll system and cultural organization to the performance of theemployees. The object of the research is PT Sampurna Motor. The observation period is conducted in 2014. Thedata is the primary data, it is the primary data which is used in this research i.e. observation, andquestionnaires. The method of the research is quantitative whereas the analysis technique has been carried out inthis research by using multiple linear regressions analysis. The research instrument is in the form ofquestionnaires which are issued to the employees of PT Sampurna Motor. The result of the research shows thatthe payroll system variable has significant and positive influence to the performance of the employees. It meansthat when the payroll system in the company is getting better, so the performance of the company will increaseas well. The cultural organization variable has significant and positive influence to the performance of theemployees. It means that the success of an organization in achieving its objective can improve the performance ofthe employees.Keywords: Payroll System, Organization Culture, Performance of the Employees